Antimicrobial stewardship in a Gastroenterology Department: Impact on antimicrobial consumption, antimicrobial resistance and clinical outcome. Issue 10 (October 2016) - Bedini, Andrea; De Maria, Nicola; Del Buono, Mariagrazia; Bianchini, Marcello; Mancini, Mauro; Binda, Cecilia; Brasacchio, Andrea; Orlando, Gabriella; Franceschini, Erica; Meschiari, Marianna; Sartini, Alessandro; Zona, Stefano; et al.
Abstract: Background: A major cause of the increase in antimicrobial resistance is the inappropriate use of antimicrobials. Aims: To evaluate the impact on antimicrobial consumption and clinical outcome of an antimicrobial stewardship program in an Italian Gastroenterology Department. Methods: Between October 2014 and September 2015 (period B), a specialist in infectious diseases (ID) controlled all antimicrobial prescriptions and decided about the therapy in agreement with gastroenterologists. The defined daily doses of antimicrobials (DDDs), incidence of MDR-infections, mean length of stay and overall in-hospital mortality rate were compared with those of the same period in the previous 12-months (period A). Results: During period B, the ID specialist performed 304 consultations: antimicrobials were continued in 44.4% of the cases, discontinued in 13.8%, not recommended in 12.1%, de-escalated 9.9%, escalated in 7.9%, and started in 4.0%. Comparing the 2 periods, we observed a decreased of antibiotics consumption (from 109.81 to 78.45 DDDs/100 patient-days, p  = 0.0005), antifungals (from 41.28 to 24.75 DDDs/100pd, p  = 0.0004), carbapenems (from 15.99 to 6.80 DDDsx100pd, p  = 0.0032), quinolones (from 35.79 to 17.82 DDDsx100pd, p  = 0.0079). No differences were observed in incidence of MDR-infections, length of hospital stay (LOS), and mortality rate. Conclusions: ASP program had a positive impact on reducing the consumption of antimicrobials, without an increase in LOS and mortality.